The human gut phageome: composition, development, and alterations in disease - Zhang, Yingying; Wang, Ran (Frontiers in Microbiology, 2023)
The human gastrointestinal tract are colonized by a large number of microorganisms, including bacteria, archaea, viruses, and eukaryotes. The bacterial community has been widely confirmed to have a significant impact on human health, while the viruses, particularly phages, have received less attention. Phages, are viruses that specifically infects bacteria. They are abundant in the biosphere and exist in a symbiotic relationship with their host bacteria. Although the application of high-throughput sequencing and bioinformatics technology has greatly improved our understanding of the genomic diversity, taxonomic composition, and spatio-temporal dynamics of the human gut phageome, there is still a large portion of sequencing data that is uncharacterised. Preliminary studies have predicted that the phages play a crucial role in driving microbial ecology and evolution. Prior to exploring the function of phages, it is necessary to address the obstacles that establish a comprehensive sequencing database with sufficient biological properties and understanding the impact of phage-bacteria interactions on human health. In this paper, we provide an overview of the human gut phageome, including its composition, structure, and development. We also explore the various factors that may influence the phageome based on current research, including age, diet, ethnicity and geographical location.Additionally, we summarize the relationship between the phageome and human disease, such as IBD, IBS, obesity, diabetes and metabolic syndrome.